Bioelectronic Medicine
Bioelectronic Medicine is an open access journal that focuses on the scientific discipline that brings together molecular medicine, bioengineering, and neuroscience to discover and develop nerve stimulating and sensing technologies to diagnose and regulate biological processes and treat disease. At the core of bioelectronic medicine is the electrical signal used by the nervous system to communicate information. Virtually every cell in the body is directly or indirectly controlled by these neural signals. Bioelectronic medicine technologies can record, stimulate and block neural signaling. Through its ability to manipulate neural signals, bioelectronic medicine will change the way physicians treat diseases and conditions such as rheumatoid arthritis, Crohn's disease, diabetes, paralysis, bleeding and even cancer. Bioelectronic Medicine brings together an expanded community and multidisciplinary audience from healthcare, technology and scientific research. Specialists come from fields such as neuroscience, biology, bioengineering, electronics, computing, data analytics, molecular medicine, pharmaceuticals, medical devices, and personalized medicine.